FEATURES OF DIAGNOSIS, TREATMENT AND REHABILITATION SECONDARY DEFORMA-TIONS OF MAXILLODENTAL SYSTEMS - Belyaev, E.V. (World of Medicine and Biology, 2015)
The paper presents the reasons for early removal of teeth in children and adults. Described indications for tooth extraction and the consequences arising from the loss of temporary and permanent teeth. Analyzed the results of domestic and international epidemiological surveys on the subject of maxillodental anomalies and deformities, outlines areas of treatment and rehabilitation of this disease. Separately allocated work based on anthropological approach to the study of secondary deformations of maxillodental system.
Keywords: secondary teeth and jaws deformation; diagnosis; treatment; anthropological features